The roles and perceptions of career guidance teachers in influencing learners' choice of nursing as a career - Sathekge, Hazel Sadie (My University, 2014)
Career guidance teachers have an important role to play in the career choices of high school learners by presenting them with information on different careers so that informed decisions can be made. It follows that the amount and quality of information that such teachers have and their views or perceptions of a career may have either a positive or negative influence on learners’ choices, in this instance, nursing as a career choice. High school learners’ declining interest in nursing as a career of choice has led to questions about career guidance teachers’ knowledge regarding nursing as a career, the attributes and contemporary roles of nurses and to what extent they suggest nursing to enquiring learners. If career guidance teachers’ perceptions about nursing influence recruitment into the profession, then it is important to determine what these perceptions are and what role they play in suggesting or not suggesting nursing as a career to high school learners. The purpose of the study was to determine the perceptions of career guidance or Life Orientation (LO) teachers in influencing high school learners’ choosing or not choosing nursing as a career. The study was delimited to Life Orientation teachers of three Johannesburg districts in Gauteng. The study objectives were to determine the frequency and source of requests for nursing information directed to career guidance teachers; to explore what career guidance teachers believe are important attributes of nurses; to determine the type of student in respect of personality and academic attributes that career guidance teachers would typically refer to a nursing programme, and to determine career guidance teachers’ perceptions of the roles and responsibilities of nurses currently and in the future. Data were collected in 2011 from September to December. The results showed that Life Orientation (LO) teachers in Gauteng do not receive a high number of requests about nursing from neither learners nor parents; just over 40% receive between one to five learner requests per year. A few teachers have suggested nursing to approximately 20 learners in the past five years; experienced teachers are more likely than inexperienced ones (p=0.0139) to suggest nursing as a career; LO teachers’ age and gender have no influence on them suggesting nursing as a career. Having studied the subject Life Sciences is the most important academic variable for referral to study nursing; learners who are caring and who enjoy working with people are considered suitable for nursing; these are also ranted as the most important personality attributes, followed by being hardworking/diligent and loving. Most LO teachers (63.0%) in this study were aware that nurses’ roles have changed over time but were not knowledgeable about the extent of role change and what the roles and responsibilities of contemporary nurses are.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2014
Keywords: Nursing; Career Choice